A morte e os ambientes de terapia intensiva: as representações sociais para um grupo de profissionais de saúde - BRENDA DE LIMA PINTO DA SILVA (2023)
This study is an investigation of the social representations of death for health professionals working in intensive care settings, seeking to understand the conditions that organize and compose the representations of death for these people. It appears that the emphasis on healing and technical procedures, present in health training and professional activities, can make it difficult to reflect on the subjective dimension of human finitude, permeating professional practices, with regard to experiences with death, as well as the experience of care for terminally ill people. To elucidate how health professionals interact with death and human finitude in their daily lives, this research carried out an investigation and discussion on how death, as an object of social representation, is apprehended by this group. The study aims to analyze the social representations of death for health professionals who make up multidisciplinary teams in intensive care settings. This is qualitative research, in which data were produced through semi-structured interview scripts and a word association tool. Five interviews were conducted with physiotherapy, nursing and psychology professionals who work in intensive care settings. As a methodology for organizing and analyzing the data, the Content Analysis technique, by Laurence Bardin, was used to elucidate categories of analysis. The analysis of the categories, seeking indicators of social representations, was based on Serge Moscovici’s Theory of Social Representations. The results demonstrate, for the investigated group, the social representation of death as a passage, permeated by suffering and the need to build dignified ways of dying. The social representation of the CTI/ICU is considered to belong to the same SR system as a complex and suffering environment, both connected to the social representation of the performance as a challenging and difficult task, which, in view of the intense challenges of such practice, is aimed at an attitude of distance from the professional in relation to the person assisted, denoting the attempt to protect oneself from suffering. The remarkable interference of the experiences lived during the Covid-19 pandemic is highlighted, since the research took place during the pandemic. It is noted that death, as an object of social representation, challenges scientific knowledge, impelling subjects to anchor the ways in which they explain phenomena and organize their practices in other knowledge, such as religion. It is considered that studies of this nature help in the integration into practice of elements that delineate social representations and, therefore, the ways in which such professionals position themselves in the face of terminal illness.